Harvesting energy from pavement based on piezoelectric effects : fabrication and electric properties of piezoelectric vibrator - Li, Rui (2019)
This article demonstrates the design of a road piezoelectric transducer (PZT) through a laboratory load test, to utilize the load mechanical energy in road. PZT-5H was selected as the piezoelectric vibrator material. With the combination of the action property of low-frequency forced vibration of the pavement vehicle wheel load, a simple supported disk lap piling piezoelectric vibrator was used as the core component of the road piezoelectricity generating set. The tracking wheel-pressure test of a beam piece was used to determine the piezoelectricity generating capacity of road pavement. The maximum voltage that could be reached is 65.2 V. The primary wheel rolling impact could produce an electric energy of 0.23 mJ. The electric capacity of 0.8 kW/h could be produced per day, which can meet the demand of signal lights.